Herniation of a Pulmonary Emphysematous Bulla to Contralateral Hemithorax - Akhtar, Jamal (National Research Institute of Tuberculosis and Lung Disease, 2011)
Herniation of an emphysematous bulla is extremely rare. A 55-year-old male patient presented with complains of shortness of breath and cough for the last 10 years which had exacerbated in the last two days. The patient was a diagnosed case of chronic obstructive pulmonary disease. Chest x-ray showed bilateral hyperinflated lung fields along with loss of lung markings in left upper lobe and a thin white line in right upper lobe suggestive of wall of bulla. High resolution computed tomography of the chest revealed anterior herniation of a pulmonary bulla from left to right side across midline. Patient was put on antibiotics, hydrocortisone and aminophylline by intravenous route and nebulization of steroid and bronchodilator. However, the patient expired after 5 days following admission.